Prefabricated structures of buildings from steel thin-wall cold formed profiles Cocoon "Transformer" - Khokhrіakova D.O.; Shamrina, H.V. (Ways to Improve Construction Efficiency, 2022)
Cocoon System AG’s light steel thin-walled structures have proven their worth in numerous superstructures, extensions, exterior wall and ceiling systems, as well as complex projects by internationally renowned architects. As part of the implementation and development of lightweight construction methods, this company has developed the Cocoon "Transformer" system, represented by prefabricated wall and floor structures with varying degrees of completeness and enlargement, registered as ETA - 11/0105. The Cocoon "Transformer" system is a frame-sheathing self-supporting or load-bearing, external or internal structure, the components of which are steel thin-walled cold-formed profiles, plate materials (cladding), insulating materials and fasteners. ETA-11/0105 suggests an optimization of this structural system. The European project ELISSA was created to improve the construction of walls, floors, roofs and volumetric modules of the Cocoon "Transformer" system with improved thermal, acoustic, vibration / seismic and fire resistance characteristics, as well as to develop industrially safe methods for their application. The use of high-performance airgel thermal insulation strips in this project minimized the effect of thermal bridging in the exterior wall structure and brought the heat transfer coefficient closer to the requirements of a passive house. The new prefabricated lightweight elements ELISSA, which demonstrate a high level of energy efficiency, provide the possibility of using insulated vacuum panels (VIP) with increased strength. The increased strength of Super Insulated VIP Panels is due to the use of foils with better endurance and also encapsulated in polyurethane. However, the version of the ELISSA system using VIP panels significantly increases the cost of the wall structure, which may hinder its widespread use in Ukraine. The creation of standard economic solutions with a sufficient level of energy efficiency according to the Cocoon "Transformer" construction concept will allow, to a certain extent, to reduce the costs of restoring the housing stock of Ukraine, damaged as a result of hostilities, and solve the problem of rapid new construction to replace completely destroyed housing.